Enhancing SDGs Desa Implementation for Human Right Fulfillment in Banyumas Regency: An Empirical Judicial Analysis - Ardhanariswari, Riris; Azzahro, Fathimah; Fauzan, Muhammad; Fadzil, Rozlinda Mohamed; Hariyanto, Hariyanto (Journal of Indonesian Legal Studies, 2024)
Sustainable Development Goals Desa (SDGs Desa) are integrated efforts of village development to accelerate the achievement of sustainable development goals. Since 2021, the village government in Banyumas Regency has implemented SDGs Desa program with an achievement score of 46.94. Therefore, this study aimed to determine the implementation of SDGs Desa and increase the achievement of the program by optimizing the role of experts to fulfill human rights in Banyumas Regency. An empirical juridical method was adopted using primary data in the form of FGDs, interviews, questionnaires, and documentation studies. Furthermore, FGD was conducted with representatives of officials from 49 villages and the data was in the form of primary, secondary, and tertiary legal materials. The results showed that the SDGs Desa program was implemented in line with the village even though there were obstacles in the data collection process. These comprised server errors, and inadequate internet network conditions, including village government knowledge related to minimal system use. Conceptually, this program has similarities with the Saansad Adarsh Gram Yojana (SAGY) program in India. Future studies could be performed because the regulations regarding villages and their derivatives regulated SDGs Desa including planning, implementation, and development mechanisms. Expert assistance was also important for increasing community participation and optimizing budget allocation to harness income sources and realize their full potential.